Aesthetic evaluation of the labiolingual position of maxillary lateral incisors by orthodontists and laypersons - Xue Jiang; Zhiwei Cao; Yang Yao; Zhihe Zhao; Wen Liao (BMC, 2021)
Abstract Background The maxillary anterior teeth play a crucial role in smile aesthetics. Previous studies regarding the importance of maxillary lateral incisors for smile aesthetics concentrated on their size, incisor edge level, and inclination, etc. However, the aesthetic effect of lateral incisor movement in the spatial position has not been studied yet. Therefore, the purpose of this study was to explore the influence of the labiolingual position of maxillary lateral incisors on the aesthetic perception of smiles by orthodontists and laypersons, as well as analyze differences in this perception between male and female raters. Methods A three-dimensional (3D) dental model was generated from the photograph of a man's smile using iOrtho7.0 software (Time Angel, Wuxi, China). Based on this model, seven images were generated with different labiolingual positions of the maxillary lateral incisors in 0.5 mm increments (+ indicating labial translation, and-indicating lingual translation). The images were evaluated by 86 orthodontists and 161 laypersons using a visual analog scale, with lower scores indicating less attractiveness. Data were analyzed using Student's t test and one-way analysis of variance with post hoc test. Results There was no significant difference in smile ratings by males and females. Orthodontists assigned lower scores to all images than laypersons. The smile at + 1.5 mm was considered the least attractive by orthodontists, while smiles at + 1.5 mm and − 1.5 mm were regarded as the least attractive by laypersons. The smile at 0 mm was evaluated as the most attractive by all raters. Laypersons gave different scores to smiles at 0 or − 0.5 mm, but orthodontists did not. Conclusions The labiolingual position of maxillary lateral incisors does affect the perception of smile aesthetics. Orthodontists may rate smile aesthetics more critically than laypersons. Therefore, communication and discussion between orthodontists and patients is needed to achieve better therapeutic and aesthetic outcomes.